Evaluation of a proficiency test of 131I, 134Cs and 137Cs in maize powder. (August 2020) - Sobiech-Matura, K.; Lutter, G.; Van Ammel, R.; Marissens, G.; Hult, M.; Emteborg, H.
Abstract: In 2017, JRC-Geel organised a proficiency test for 120 participants on the massic activity determination of 131 I, 134 Cs and 137 Cs in maize powder. The proficiency test reference material was produced by spiking blank maize powder. The material was characterised for its radioactive content using γ -ray spectrometry. The z scores of the reported massic activity were acceptable in 92% of the results for 131 I, and in 94% for both 134 Cs and 137 Cs. The ζ scores were consistent with the reference value for 66% of the results for 131 I, 56% for 134 Cs and 68% for 137 Cs. Highlights: Proficiency test reference material prepared by spiking. 120 European laboratories participated in the PT. More than 90% of satisfactory results according to z score evaluation. Improvement of uncertainty estimation needed in around one third of submitted results.